Study on the influence of gas components on the application of relevant standards to coal seam gas content and revision suggestions - Yujin QIN; Wenjin HOU; Weiwei SU; Zhanyou SA; Shouqing LU; Jie LIU; Zhongyu ZHENG (Meikuang Anquan)
As the core parameter of coal seam gas occurrence, the scientific definition and standardized application of coal seam gas content has important guiding significance for coal mine gas resource development and disaster prevention. Based on the existing determination of coal seam gas content and the applicable standards in China, by employing methods such as literature review, data statistics, theoretical calculation and analysis, in-depth exploration and analysis have been carried out on the issues emerging in the three crucial domains of gas emission quantity prediction, gas drainage projection and assessment of the risk of coal and gas outburst due to the failure to systematically talk into account the impact of non-CH4 gas components on gas content. Furthermore, suggestions for the revision have been put forward for the relevant determination standards of coal seam gas content and the relevant standards that reference them. The research show that the gas components of coal seam in China generally exhibit a multi-component gas characteristics with CH4 being the predominant component, accompanied by N2 and CO2; when the volume fraction of CH4 in the coal seam is lower than 90%, this gives rise to a considerably large systematic deviation in the prediction results of gas sub-sources within the mine, distorted statistical data of gas resources and incorrect conclusions during the assessment of outburst danger. Consequently, the impact of gas components must be taken into account, especially when the gas pressure is calculated using the indirect method, which cannot be neglected. It is recommended that precisely demarcating the definition boundaries of “coal seam gas content (including non-flammable gas)”, “flammable gas content in coal seam” and “methane content in coal seam”. In the course of engineering application, the three terms mentioned above should be cited normatively in accordance with actual demands. Over the prospective period, in-depth studies can be conducted on the influence mechanism of competitive adsorption of different gas components on gas pressure, further improving the theory of coal seam gas occurrence and precisely directing the prevention and control of coal mine gas in China.